2001
DOI: 10.2214/ajr.176.2.1760447
|View full text |Cite
|
Sign up to set email alerts
|

Power Injection of Contrast Media Using Central Venous Catheters

Abstract: Power injection of contrast media through central venous catheters for CT examinations is feasible and safe when set hospital guidelines and injection protocols are followed. This technique provides an acceptable alternative in patients without adequate peripheral IV access when bolus contrast enhancement is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…A number of studies have addressed the issue of what level of hepatic enhancement constitutes the minimum acceptable for liver imaging: 30 HU [70], 40 HU [71][72][73], or 50 HU [9,33,[74][75][76][77]. In a multi-center study Megibow et al [19] found that 30 HU was the lowest limit of acceptable hepatic enhancement and that no definite clinical gain was achieved with hepatic enhancement greater than 50 HU.…”
Section: Contrast Enhancement Magnitudementioning
confidence: 99%
“…A number of studies have addressed the issue of what level of hepatic enhancement constitutes the minimum acceptable for liver imaging: 30 HU [70], 40 HU [71][72][73], or 50 HU [9,33,[74][75][76][77]. In a multi-center study Megibow et al [19] found that 30 HU was the lowest limit of acceptable hepatic enhancement and that no definite clinical gain was achieved with hepatic enhancement greater than 50 HU.…”
Section: Contrast Enhancement Magnitudementioning
confidence: 99%
“…during contrast-enhanced CT (ceCT), or were limited regarding injection pressure and flow [6]. Power contrast injections via TIVAPs have been evaluated in vitro, but only a few data on in vivo use of power injections via TIVAPs exist [6][7][8].…”
mentioning
confidence: 99%
“…during contrast-enhanced CT (ceCT), or were limited regarding injection pressure and flow [6]. Power contrast injections via TIVAPs have been evaluated in vitro, but only a few data on in vivo use of power injections via TIVAPs exist [6][7][8]. Recently, devices approved for power contrast injections (totally implantable venous power ports, TIVPPs) have been developed, but until today literature regarding the safety and use of power injections via these devices is limited to only one study on chest ports [9].…”
mentioning
confidence: 99%
“…Confirmation of reflux from the injection route has been reported as a safety countermeasure during power injection [3,[9][10][11]. In some reports, the saline test injection was performed manually [2,3,12].…”
Section: Discussionmentioning
confidence: 99%